Coping with water supply interruptions: can citizen voice in transdisciplinary research make a difference?. Issue 5 (4th July 2018) - Hamer, Nicholas G.; Lipile, Liema; Lipile, Mbulelo; Molony, Lara; Nzwana, Xolelwa; O'Keeffe, Jay; Shackleton, Sheona E.; Weaver, Matthew; Palmer, Carolyn G.
ABSTRACT: Despite explicit legal and policy commitments, many South African residents do not have reliable access to potable water. Resident dissatisfaction with municipal water service delivery is evidenced by frequent civil protests. We consider how gathering and understanding the lived experiences of citizens could influence official responses to water interruptions. We take a transdisciplinary, problem-focussed, research approach to the experience of, and responses to, water interruptions, reflecting on the limitations of research to effect change in the lived experience. As transdisciplinary research praxis increasingly seeks expression in social outcomes, it is vital to confront both opportunities and limitations.